Who gains more from which infrastructure in rural People's Republic of China? - Guanghua Wan; Xun Zhang (Asian Development Bank Institute (ADBI), 2015)
Since the oil price shocks of the 1970s, several studies have found significant impacts of oil prices on macro variables. However, it is particularly crucial to know how each micro sector in an economy, such as the residential, transport, industrial and non-energy sectors, respond to oil price impulses. In this research, we try to shed light on the impact of crude oil price volatility on each sector in Japan, the world's third-largest crude oil consumer. In order to do so, we apply a vector auto regression model and perform impulse response analysis by using quarterly data from Q1 1990 to Q1 2014. The findings indicate that some economic sectors, such as the residential sector, did not have significant sensitivity to the sharp oil price fluctuations. In contrast, some other sectors, like the commercial, industrial, and transport sectors, were strongly sensitive to the drastic oil price fluctuations. Moreover, our findings show that after the Fukushima disaster in 2011, which led to the shutdown of nuclear power plants in Japan, because of greater reliance on oil imports, the sensitivity of most sectors to oil price volatility declined.
Keywords: C32; O49; Q43; 330